Determinants of Green Purchase Behavior of Local Coffee Shop: The Moderating Impact of Price Sensitivity - Nadhita Az-Zahrah; Donni Junipriansa; Joko Rizkie Widokarti (Journal of Consumer Sciences)
Background: Indonesia has a significant plastic waste problem, despite increasing consumer awareness of environmental issues. This highlights the need for further research into factors influencing green purchase behavior (GPB), especially within the rapidly growing coffee shop sector. As coffee consumption surges, local coffee shops like Point Coffee Yogyakarta have grown substantially.